APPLICATION OF WORK BREAKDOWN STRUCTURE (WBS) AND GANTT CHART ON THE PROJECT OF COMPOSING CURRICULUM MERDEKA BELAJAR KAMPUS MERDEKA - Padmakusumah, Rizal Ramdan; Suraji, Entol; Umam, Muhammad Khoirul; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Revision of Compilation Curriculum Merdeka Belajar Kampus Merdeka (Proyek MBKM) is a Strategic Project for the Widyatama University Undergraduate Management Study Program. The purpose of this research is to try to apply the operations management method, namely the work breakdown structure (WBS) and Gantt Charts as a tool in scheduling and calculating the completion time of the MBKM Project. This type of research is a qualitative research. The data analysis method is using WBS and Gantt Charts combined with Focus Group Discussion (FGD). The results showed that the calculation of project completion time without the use of a combination of WBS and Gantt Chart methods resulted in a longer project completion time calculation. The conclusion of this research is that WBS and Gantt Chart are very helpful in scheduling and calculating project completion time better and more accurately.